"Out of Care" HIV Case Investigations: A Collaborative Analysis Across 6 States in the Northwest US. (1st February 2017) - Dombrowski, Julia C.; Bove, Joanna; Roscoe, James C.; Harvill, Jessica; Firth, Caislin L.; Khormooji, Shireen; Carr, Jason; Choi, Peter; Smith, Courtney; Schafer, Sean D.; Golden, Matthew R.
Abstract : Background: HIV care continuum estimates derived from laboratory surveillance typically assume that persons without recently reported CD4 count or viral load results are out of care. Methods: We conducted a multistate project (Alaska, Idaho, Montana, Oregon, Washington, and Wyoming) to ascertain the status of HIV cases that appeared to be out of care during a 12-month period. We used laboratory surveillance to identify cases in all states but Idaho, where viral load reporting is not mandatory, requiring us to rely on clinic records. After complete investigation, we assigned each case one of the following dispositions: moved out of state, died, in HIV care, no evidence of HIV care, or data error. Results: We identified 3866 cases with no CD4 count or viral load result in a ≥12-month period during 2012–2014, most (85%) of which were in Washington or Oregon. A median of 43% (range: 20%–67%) of cases investigated in each state had moved, 9% (0%–16%) had died, and 11% (8%–33%) were in care during the 12-month surveillance period. Only 28% of investigated cases in the region and a median of 30% (10%–57%) of investigated cases in each state had no evidence of care, migration, or death after investigation. Conclusions: Most persons living with HIV in the Northwest United States who appear to be out of care based on laboratory surveillance are not truly out of care. Our findings highlight the importance of improving state surveillance systems to ensure accurate care continuum estimates and guide Data to Care efforts. Abstract : Supplemental Digital Content is Available in the Text.